EFT, Kebutuhan Tidur, Lansia PENGARUH EMOTIONAL FREEDOM TECHNIQUE (EFT) TERHADAP PEMENUHAN KEBUTUHAN TIDUR PADA LANSIA: EFFECT OF EMOTIONAL FREEDOM TECHNIQUE (EFT) ON FULFILLING THE NEEDS OF SLEEP ON ELDERLY - Kartikasari, Betti Dwi (Jurnal Keperawatan Malang, 2017)
Abstract Elderly experience inevitably aging process that causes them to experience many changes, such as anatomy/physical, disease or pathological conditions, and and psychosocial effects on organ function that will cause various health problems one of them is sleep depriviation. This research goal is to identify the effects of Emotional Freedom Technique on Fulfillment of the need of sleep in the elderly. Pretest – Postest Designis used, and 23 respondents were obtained. Pittsburgh Sleep Quality Index (PSQI) questionnaire is used to obtain data. Wilcoxon Signed Rank analysis is used to analyze the data. Analysis shows that p<0.05 (0.001). it can be inferred that there is effect or differences of Fulfillment of the need of sleep between before anda after EFT intervention. The existence of this influence is caused by the element of relaxation and positive suggestion in the intervention of Emotional Freedom Technique (EFT). Keywords: Elderly, Fulfillment of the need of sleep, EFT